A comparative study on short term surgical outcome between laparoscopic inguinal hernia mesh repair vs. open inguinal hernia mesh repair for primary unilateral inguinal hernias - Thulasilingam, Kathirazhagan; Akhter, Jameel (International Surgery Journal, 2023)
Background: Current study was performed to compare the short-term surgical outcome of laparoscopic (TAPP) and open inguinal hernia mesh hernioplasty (Lichtenstein) in primary unilateral inguinal hernias such as time taken by patients to return to routine daily activities and return to work. Methods: This is a prospective, comparative study done in Apollo Main Hospital, Chennai comparing surgical outcomes between laparoscopic and open primary unilateral inguinal hernia mesh repair in a total of 60 patients with 30 patients in each arm. Results: Return to Job is 8 median days in laparoscopic group and 9 median days in open group which is significant with a p value of 0.000. Pain score at 12th hour is significantly lesser in laparoscopic group with a VAS score of 3 compared to open group with a VAS score of 4 with p value of 0.015. VAS score at POD 1 in laparoscopic group is 2 and in open group is 3 which is significantly lesser in laparoscopic group with a p value of 0.026. Pain score at POD 3 and 4 is significantly lesser in laparoscopic group with a p value of 0.001 and 0.008 respectively. laparoscopic group takes analgesia for a lesser number of days than the open group with a p value of 0.019. Conclusions: This study concludes laparoscopic repair for primary unilateral inguinal hernias is superior to Lichtenstein tension free mesh hernioplasty in terms of postoperative pain, early return to job and less consumption of postoperative analgesia.